2023
DOI: 10.1002/ajb2.16122
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the components of pollen limitation in a widespread herb with gametophytic self‐incompatibility

Abstract: Premise Seed production is frequently limited by the receipt of insufficient or low‐quality pollen, collectively termed “pollen limitation” (PL). In taxa with gametophytic self‐incompatibility (GSI), incompatible pollen can germinate on stigmas but pollen tubes are arrested in styles. This allows for estimates of pollen performance before, during, and after self‐recognition, as well as insight into the factors underlying pollen quality limitation in GSI taxa. Methods We scored pollen performance following self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 80 publications
(114 reference statements)
0
11
0
Order By: Relevance
“…For each flower, we averaged the number of stigmatic pollen grains, and pollen tube number across the 5 styles scored. Previous work using a subset of the samples presented here showed that results from analyses of style-level and flower-level average data were similar [36].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each flower, we averaged the number of stigmatic pollen grains, and pollen tube number across the 5 styles scored. Previous work using a subset of the samples presented here showed that results from analyses of style-level and flower-level average data were similar [36].…”
Section: Methodsmentioning
confidence: 99%
“…To quantify components of pollen quality and quality limitation in A. anserina populations, we assessed prezygotic stages of fertilization success from open-pollinated flowers collected in the field [29,36,[40][41][42][43][44]. We collected styles from senesced flowers in 13 populations of A. anserina during peak flowering in July of 2019, 2020 and 2021.…”
Section: (B) Style Processing and Scoringmentioning
confidence: 99%
See 2 more Smart Citations
“…(Rosaceae) is a perennial herb, with a cosmopolitan global distribution in temperate environments. It reproduces both sexually via self-incompatible flowers (Cisternas-Fuentes et al 2023 ), and vegetatively via runners (Eriksson 1988 ). Flowers of anserina are predominately pollinated by small solitary bees and flies (Koski and Ashman 2015 ).…”
Section: Methodsmentioning
confidence: 99%